Pengembangan Mobile Game based Learning Kosakata Bahasa Arab untuk Siswa Kelas 3 Sekolah Dasar - Hanik Farida; Saida Ulfa; Dedi Kuswandi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
Technological development encourages various innovations in learning, one of them is game based learning. This research aims to develop a mobile game for learning Arabic vocabulary for elementary school students in grade 3. This research is a development research, with the development research model of Lee and Owen. The technique for collecting data is through distributing questionnaires. It was validated first by media and material experts before being tested on students. From the validation, the percentage eligibility of the media was 98.75 percent, and the feasibility of the material was 81.25 percent. These results indicate this game feasible continued trial phase for student and obtained a product eligibility percentage of 84.65 percent means that the game is valid and feasible in learning Arabic vocabulary for grade 3 elementary school students.